2012
DOI: 10.4018/jdet.2012070103
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Organization and Generation of Presentation Slides for E-Learning

Abstract: The effectiveness of an e-learning system for distance education to a large extent depends on the relevancy and presentation of learning content to the learner. The ability to gather documents on a particular topic from the web and adapt the contents of the document to suit the learner is an important task from the content creation perspective of e-learning. For the developer of e-learning material the provision to automatically extract, organize, and present content material would improve its effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Others Classification Others This paper describe a repository of learning objects which automatically organizes the content in clusters of semantic proximity by the use of text mining. (Sathiyamurthy & Geetha, 2012) Others…”
Section: Figueira 2008amentioning
confidence: 99%
“…Others Classification Others This paper describe a repository of learning objects which automatically organizes the content in clusters of semantic proximity by the use of text mining. (Sathiyamurthy & Geetha, 2012) Others…”
Section: Figueira 2008amentioning
confidence: 99%
“…Over the past decade, researchers have investigated different pedagogical strategies for making the online learning environment effective. Sathiyamurthy & Geetha (2012) state that "The effectiveness of an e-learning system for distance education to a large extent depends on the relevancy and presentation of learning content to the learner". In a recent study, Kim & Reeves (2007) showed that the increase in online courses has definitely helped to reach millions of learners, but the educational effectiveness of online courses is a subject of debate.…”
Section: Related Researchmentioning
confidence: 99%
“…content presentation environment and self-regulated learning strategies. The effectiveness of an e-learning system depends on the relevancy and presentation of learning content to the learner [7]. The content presentation approach enables the user to explore further information in the context of the current learning topic.…”
Section: Cognitive Learning Processmentioning
confidence: 99%